Promosi, Harga dan Kualitas Jasa terhadap Keputusan Pembelian Konsumen pada PT. Qubic Ball Dot Com - Khomeiny Yunior; Wylie Raynaldo (IPM2KPE, 2024)
The purpose study was to examine the effect of promotion, price and product quality on purchasing decisions on the Effect of Promotion, Price and Service Quality on consumer purchasing decisions at PT Qubic Ball Dot Com, Medan. The population in this study amounted to 167 customers and the sample in this study amounted to 118 customers. The sampling method is simple random sampling method. The research method used is using quantitative research methods, the type of research is descriptive, the type of data is the answer to the questionnaire. This research was conducted with validity and reliability tests and classical assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests. The results of this study indicate that partially the promotion variable obtained the value of t count> t table or 3.218> 1.98099 and significant 0.002 <0.05, the price variable obtained the value of tcount> t table or 2.610 1.98099 and significant 0.010 <0.05, The product quality variable obtained a tcount> ttable value or 2.266> 1.98099 and a significant 0.025 <0.05, the coefficient of determination test results show 36.1% of the explained variables, while the remaining 63.9% is explained by other variables not used in this study. The conclusion of this study is that promotion has a negative and significant effect on buyer decisions, price has a positive and significant effect on buyer decisions, product quality has a positive and significant effect on buyer decisions. Promotion, price and product quality have a simultaneous effect on buying decisions on the Effect of Promotion, Price and Service Quality on consumer purchasing decisions at PT. Qubic Ball Dot. Keywords : Service Quality, Purchasing Decisions, Promotion, Price